2022
DOI: 10.3390/plants11111403
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Assessment of the International Maize and Wheat Improvement Center and Chinese Wheat Core Germplasms by Non-Denaturing Fluorescence In Situ Hybridization

Abstract: Germplasm is the material basis for crop genetic improvement and related basic research. Knowledge of genetic diversity present in wheat is the prerequisite for wheat breeding and improvement. Non-denaturing fluorescence in situ hybridization (ND-FISH) is a powerful tool to distinguish chromosomal polymorphisms and evaluate genetic diversity in wheat. In this study, ND-FISH using Oligo-pSc119.2-1, Oligo-pTa535-1, and Oligo-(GAA)7 as probes were used to analyze the genetic diversity among 60 International Maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Similar to other studies of genetic divergence, the Tocher method used here also showed a trend towards the formation of a larger group and genotypes isolated in other groups [60][61][62]. Multivariate analyses, such as Tocher (Table 4) and UPMG (Figure 2), are powerful tools to assist in the characterization [63] and discrimination of genotypes [64,65] and should be extensively used in genetic diversity studies [66][67][68]. Understanding genetic diversity is one of the fundamental steps within genetic improvement programs, with the multivariate analysis approach being the most commonly used [69].…”
Section: Discussionsupporting
confidence: 73%
“…Similar to other studies of genetic divergence, the Tocher method used here also showed a trend towards the formation of a larger group and genotypes isolated in other groups [60][61][62]. Multivariate analyses, such as Tocher (Table 4) and UPMG (Figure 2), are powerful tools to assist in the characterization [63] and discrimination of genotypes [64,65] and should be extensively used in genetic diversity studies [66][67][68]. Understanding genetic diversity is one of the fundamental steps within genetic improvement programs, with the multivariate analysis approach being the most commonly used [69].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, some Chinese wheat cultivars were derived from the IMC founders Nanda2419, Orofen, and Early Premium (Tables S1 and S3, Figure S11). These results demonstrated the influence of exotic germplasms in Chinese wheat breeding (Li et al, 2022;Yang et al, 2022;Zhuang, 2003). These introductions and the wide usage of foreign cultivars in Chinese wheat breeding promoted accumulation of new SCVs that appear only in MCCs, indicating that these genes were relatively important in breeding (Hao et al, 2020).…”
Section: Chromosome Evolution Of Chinese Wheat During Cultivar Develo...mentioning
confidence: 79%
“…Improvement of TKW is considered to be an important step for further increasing the yield potential in various parts of the world (Rasheed et al, 2014;Yang et al, 2022). The major contribution made by SHW-L1 to the high yield potential of three Shumai varieties relates to improvements in TGW (thousand-grain weight).…”
Section: Relationship Between Grain Protein Content and Grainmentioning
confidence: 99%
“…Williams and Sorrells (2014) conducted QTL mapping in populations derived from SHW and identified several loci on 3D and 6D chromosomes that underpin grainrelated traits, including TKW (Börner et al, 2015). Several authors reviewed the current status of synthetic-derived wheat cultivars (Chuanmai 28,42,43,47,64,104) released in Southwestern China (Li et al, 2014;Yang et al, 2022). This rise was mainly associated with an increase in seed weight, number of spikes per m 2 , and the number of seeds per spike (Cooper et al, 2013;Aberkane et al, 2020).…”
Section: Relationship Between Grain Protein Content and Grainmentioning
confidence: 99%